The World Almanac and Book of Facts 2004 - Edited by McGeveran, William A. (New York World Almanac Books, 2004)
This book includes a month-by-month report of major national and international news stories, in-depth coverage of sports, facts behind the news, expanded Internet information, expanded information on states and countries, and much more
Include Color Illustration
Keywords: Almanacs, American -- Statistics